2021
DOI: 10.4081/hr.2021.8847
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term and Quality of Survival in Patients Treated for Acute Lymphoblastic Leukemia during the Pediatric Age

Abstract: Long-term survival for acute lymphoblastic leukemia (ALL) in children improved over the last three decades up to 80-90% of affected patients. Consequently, the quality of life of survivors has become increasingly important. This study analyses the clinical features and outcome of 119 children with ALL, focusing on the quality of long-term survival in a subset of 22 patients over 18 years of age. Among this group, the 10-year event-free survival and overall survival were 83.1% (C.I. 74.0-89.2) and 88.4% (C.I. 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The development of effective treatments and well‐designed clinical protocols have resulted in a dramatic increase of the long‐term outcome of ALL over the last few decades, with overall survival rates exceeding 90%, and without compromising the quality of life of survivors. 21 , 22 The bacterial‐derived enzymes, asparaginases, are among the drugs used in the treatment of ALL, with E. coli asparaginase, a pegylated form of the native E. coli asparaginase, and an enzyme isolated from Erwinia as the three main types. Other novel forms of recombinant E. coli asparaginase 23 and a pegylated recombinant formulation of Erwinia asparaginase 24 have been recently developed and are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The development of effective treatments and well‐designed clinical protocols have resulted in a dramatic increase of the long‐term outcome of ALL over the last few decades, with overall survival rates exceeding 90%, and without compromising the quality of life of survivors. 21 , 22 The bacterial‐derived enzymes, asparaginases, are among the drugs used in the treatment of ALL, with E. coli asparaginase, a pegylated form of the native E. coli asparaginase, and an enzyme isolated from Erwinia as the three main types. Other novel forms of recombinant E. coli asparaginase 23 and a pegylated recombinant formulation of Erwinia asparaginase 24 have been recently developed and are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The data were obtained from medical records of all childhood ALL patients presenting with hyperleukocytosis to our facility and who underwent exchange transfusion within the time frame specified. The inclusion criteria were ALL patients aged 0-19 years with leukocyte counts above 100x10 9 /L, treated with exchange transfusion, and complete medical records of the pre-and post-therapy clinical and laboratory data. The exclusion criteria was medical records that lacked data outcomes., death before the exchange This study was approved by the Ethics Committee of the Faculty of Medicine, Universitas Airlangga.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown improved 5-year overall survival rates exceeding 90%, and the current treatment is considered to be well-tolerated and does not impair survivors' quality of life. 8,9 Even with such significantly satisfactory outcomes, complications and emergencies in ALL still require immense consideration. Hyperleukocytosis, reported in 9-13% of children with ALL, is one of the complications and a risk factor for early morbidity and mortality, as well as poor outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell precursor acute lymphoblastic leukemia (T-ALL) represents approximately 10% of all pediatric cases (2)(3)(4)(5)(6). Despite progress made through innovative therapies and treatment regimens, achieving disease-free survival rates of 90% in developed countries, hematological malignancies in children persist as the leading cause of disease-related deaths globally (1,7).…”
Section: Introductionmentioning
confidence: 99%